Moderate-Load Muscular Endurance Strength Training Did Not Improve Peak Power or Functional Capacity in Older Men and Women - Walker, Simon; Haff, Guy G.; Häkkinen, Keijo; Newton, Robert U. (Frontiers in Physiology, 2017)
The present study determined the effects of muscular endurance strength training on maximum strength and power, functional capacity, muscle activation and hypertrophy in older men and women. Eighty-one men and women acted as an intervention group while 22 acted as non-training controls (age range 64-75y). Intervention training included super-sets (i.e. paired exercises, immediately performing the second exercises following completion of the first) with short rest intervals (30-60s between sets) at an intensity of 50‒60% one-repetition maximum (1-RM) for 15-20 repetitions. Concentric leg press actions measured maximum strength (1-RM) and concentric peak power. Functional capacity was assessed by maximum speed walking tests (i.e. forward walk, backward walk, timed-up-and-go and stair climb tests). Quadriceps muscle activation was assessed by surface electromyogram and twitch interpolation technique. Vastus lateralis cross-sectional area was measured by panoramic ultrasound. Compared to control, the intervention groups increased maximum strength (1-RM; men: 10±7% vs. 2±3%, women: 14±9% vs. 1±6% both P<0.01) and vastus lateralis cross-sectional area (men: 6±7% vs. -3±6%, women: 10±10% vs. 0±4% both P<0.05). But there were no between-group differences in peak power, muscle activation or functional capacity (e.g. stair climb; men: -5±7% vs. -4±3%, women: -5±6% vs. -2±5% both P>0.05). While benefits occurred during muscular endurance strength training, specific stimuli are probably needed to target all aspects of age-related health.